Checklist of Gastrotricha of the Polish Baltic Sea with the first reports of Heterolepidoderma joermungandri Kånneby, 2011, and Turbanella hyalina Schultze, 1853 - Kolicka, Małgorzata; Kisielewski, Jacek; Kotwicki, Lech; Zawierucha, Krzysztof; Grzelak, Katarzyna (Zootaxa, 2014)
Gastrotricha is a cosmopolitan phylum of aquatic and semi-terrestrial invertebrates comprising more than 800 described species. Up to now, only five taxonomic and faunistic papers have been published on the gastrotrichs of the Polish Baltic Sea and 27 taxa have been found (including three freshwater, which were found in estuaries). This article presents a complete list of brackish and estuarine Gastrotricha from the Polish Baltic Sea accompanied by localities and the first observations of gastrotrich species inhabiting the underwater macrophytes. Although the group has been studied for more than 150 years, the gastrotrich community of marine macrophytes has not been studied in any great detail. Here we provide data on gastrotrich communities living on macrophytes and also in sandy sediments. In total, nine species were found (seven from sandy sediments, two species from macrophytes). Seven of the species belong to Chaetonotida: Halichaetonotus balticus Kisielewski, 1975, H. lamellatus Kisielewski, 1975, H. schromi Kisielewski, 1975, Heterolepidoderma joermungandri Kånneby, 2011, Lepidodermella squamata (Dujardin, 1841), Xenotrichula intermedia Remane, 1934, and X. velox Remane, 1927(c). Two of species belong to Macrodasyida: Turbanella cornuta Remane, 1925, and T. hyalina Schultze, 1853. H. joermungandri and T. hyalina are new for Polish fauna. Both species correspond with the original descriptions but differ by some morphometric characters. Taxonomic, morphometric, and biogeographic remarks are provided for the new records together with differential interference contrast (DIC) microphotographs.